Competitive Advantage and Intellectual Capital as Mediators of the Influence of Corporate Governance on Firm Value - Gede Putu Agus Jana Susila; I. B. Anom Purbawangsa; Henny Rahyuda; Luh Gede Sri Artini (Jurnal Ilmiah Akuntansi, 2023)
This study aims to test and explain the relationships between corporate governance, firm values, competitive advantage, and intellectual capital. This research is explanatory research using quantitative research designs conducted on companies participating in the Asean Corporate Governance Scorecard assessment from six countries, namely Indonesia, Malaysia, Thailand, Singapore, the Philippines and Vietnam during 2019 to 2021. The total population in this study was 135 companies based on ASEAN asset classes per Country, 2019, namely: 10 companies for Indonesia, 37 companies for Malaysia, 19 companies for the Philippines, 26 companies for Singapore, 42 companies for Thailand, 1 company for Vietnam. ASEAN asset class award recipients consist of diverse companies from the financial, industrial, goods and services, consumer, property, energy, telecommunications and media sectors. The results show that (1) corporate governance have a negative effect on the company's firm value, (2) corporate governance have a positive effect on competitive advantage, (3) corporate governance have a positive influence on intellectual capital, (4) intellectual capital have a positive effect on firm value, (5) intellectual capital has a positive influence on competitive advantage, and (6) competitive advantage v has a positive effect on firm value.